Effect of Moisture Content on the Ductility of Cemented Paste Backfill. Issue 2 (May 2020) - Wang, Yongyan; Yu, Zhuoqun; Cui, Lizhuang; Wang, Yong
Abstract: The ductility of cemented paste backfill at different moisture content were researched in this paper. The cemented paste backfill specimens at three different moisture content were prepared and the uniaxial compressive tests were conducted. The results show that the compressive strength of specimen decreases with the increase of moisture content. However, the ductility of specimen increases with the increase of moisture content. The elastic modulus and the rate of post peak stress reduction decreases with the increase of moisture content. The obtained results are helpful to better understand the behavior of the cemented paste backfill under different moisture condition, which could provide guidance for safe mining.